Extent of services supported by Q-signaling over IP - Voznak, Miroslav (Communications - Scientific letters of the University of Zilina, 2004)
QSIG is a signaling protocol used for interconnection of various telecommunication systems in corporate networks. These networks are composed of homogeneous or heterogeneous elements. Basic procedures of connection and supplementary services are transferred through messages, which are defined in recommendations ETSI or ISO. QSIG can be used for transport proprietary signaling between the same PBXs and is supported in voice gateway of solution of Voice over IP too and environment of IP network is often chosen for interconnection between PBXs. The main aim of this paper is to acquaint specialists with the result of the QSIG compatibility test between Siemens and Cisco. Siemens produces one of the most used telecommunication systems in the Czech republic and Cisco systems routers are the most used in IP solutions. In order to provide all supplementary services in telecommunication, Siemens developed a new protocol, called CorNet-NQ, which is a superset of QSIG and uses messages tunnelling through QSIG. For realization of this test the QSIG version PSS1V2 in agreement with the ISO standards was used. [1]